Jociles, María Isabel and Adela Franzé (eds.) Is the school the problem ?: Socio-anthropological perspectives on ethnography and education. Madrid: trotta, 2008, 414 pp. - Martínez Alamillo, Laura (2009)
The review does not present a summary.